2019
DOI: 10.1080/02670844.2018.1451612
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic behaviour of anodised titanium using different cathodes

Abstract: In the last decades, titanium dioxide (TiO 2) has been widely researched, because of its applications in photocatalytic environmental pollution removal and in hydrogen generation. Hence, this work deals with the synthesis of titanium dioxide by anodising titanium sheets, however using different cathodes, which may induce differences in the composition and structure of the obtained oxide layers so that these suspected differences can be observed. All specimens were equally thermally treated after anodising to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
(56 reference statements)
2
5
0
Order By: Relevance
“…[ 147 ] performed anodic oxidation at 5 V and 10 V in NH 4 F/NaCl electrolyte to produce TiO 2 nanotubes. The diameters of nanotubes increased from 24-30 nm for 5 V to 35–53 nm for 10 V which matches trends in other studies with similar electrolytes [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ]. Michalska-Domańska et al.…”
Section: Factor Affecting Characteristics Of Tio 2 Layersupporting
confidence: 89%
See 4 more Smart Citations
“…[ 147 ] performed anodic oxidation at 5 V and 10 V in NH 4 F/NaCl electrolyte to produce TiO 2 nanotubes. The diameters of nanotubes increased from 24-30 nm for 5 V to 35–53 nm for 10 V which matches trends in other studies with similar electrolytes [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ]. Michalska-Domańska et al.…”
Section: Factor Affecting Characteristics Of Tio 2 Layersupporting
confidence: 89%
“…Hsu et al [147] performed anodic oxidation at 5 V and 10 V in NH 4 F/NaCl electrolyte to produce TiO 2 nanotubes. The diameters of nanotubes increased from 24-30 nm for 5 V to 35-53 nm for 10 V which matches trends in other studies with similar electrolytes [75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96]. Michalska-Doma nska et al [169] reported that the diameter of nanotubes did not grow linearly with applied voltage when fabrication was done at 30-60 V in ethanol-based electrolyte containing NH 4 F and deionised water.…”
Section: Applied Voltagesupporting
confidence: 83%
See 3 more Smart Citations